2018
DOI: 10.1088/1361-648x/aaab22
|View full text |Cite
|
Sign up to set email alerts
|

Micrometer-sized TPM emulsion droplets with surface-mobile binding groups

Abstract: Colloids coated with lipid membranes have been widely employed for fundamental studies of lipid membrane processes, biotechnological applications such as drug delivery and biosensing, and more recently, for self-assembly. The latter has been made possible by inserting DNA oligomers with covalently linked hydrophobic anchors into the membrane. The lateral mobility of the DNA linkers on micrometer-sized droplets and solid particles has opened the door to creating structures with unprecedented structural flexibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…After 1 h, the fluorescence intensity of the CSLBs with F-127 was comparable to that of control particles not coated with linker dsDNA (Figure 3 C-F). We therefore conclude that F-127 removed the cholesterol-anchored linker DNA from the bilayer, in line with recent experiments on emulsion droplets coated with mobile DNA linkers [55].…”
Section: Influence Of Free and Grafted Polymerssupporting
confidence: 91%
See 1 more Smart Citation
“…After 1 h, the fluorescence intensity of the CSLBs with F-127 was comparable to that of control particles not coated with linker dsDNA (Figure 3 C-F). We therefore conclude that F-127 removed the cholesterol-anchored linker DNA from the bilayer, in line with recent experiments on emulsion droplets coated with mobile DNA linkers [55].…”
Section: Influence Of Free and Grafted Polymerssupporting
confidence: 91%
“…Note that the slight repulsion at small angles is caused by boundary effects inherent to our analysis method. linkers, the large linker patch that is formed between particles can slow down the motion when the supporting fluid is inhomogeneous [55] and colloidal joints lose their flexibility with an increasing concentration of dsDNA linkers in the bond area [16].…”
Section: Mobility Of Self-assembled Structuresmentioning
confidence: 99%
“…Droplets offer advantages in terms of stability, robustness, and the possibility of easily generating large mono-disperse samples by means of microfluidic devices [101]. Methods for anchoring molecular linkers to oil droplets have often involved the use of phospholipids whose head groups are functionalsied with PEG-biotin anchors [17,95,[97][98][99]102]. Similar to the strategy mentioned above for DNA functionalisation of liposomes, streptavidin is then used to bridge between the lipid anchors and oligonucleotides [17,95,[97][98][99]102] or more complex DNA nanostructures [96], which then mediate multivalent interactions.…”
Section: Functionalsied Emulsion Dropletsmentioning
confidence: 99%
“…Under basic conditions, the methoxy groups of the MPTMS hydrolyze, yielding droplets. [19] While siloxane bonds are also formed at this stage, previous studies suggested that these droplets behave more liquid-like than gel-like, as droplets are able to reach energetically favourable locations. [10] After an initiator is added, the methacrylate groups polymerize -or cross-link -and the droplet solidifies.…”
Section: Introductionmentioning
confidence: 89%